2017
DOI: 10.1177/0161734617711370
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Muscle Ultrasonography Using Textural Analysis in Amyotrophic Lateral Sclerosis

Abstract: The purpose of this study was to analyze differences in gray-level co-occurrence matrix (GLCM) parameters, as assessed by muscle ultrasound (MUS), between amyotrophic lateral sclerosis (ALS) patients and healthy controls, and to compare the diagnostic accuracy of these GLCM parameters with first-order MUS parameters (echointensity [EI], echovariation [EV], and muscle thickness [MTh]) in different muscle groups. Twenty-six patients with ALS and 26 healthy subjects underwent bilateral and transverse ultrasound o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
(61 reference statements)
2
38
1
Order By: Relevance
“…Martínez‐Payá et al . (2017) also explored muscle textural analysis using the gray‐level co‐occurrence matrix (GLCM) . They used the same patients and data set as in their previously mentioned study, applying a new analysis to the images.…”
Section: Muscle Ultrasound In Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez‐Payá et al . (2017) also explored muscle textural analysis using the gray‐level co‐occurrence matrix (GLCM) . They used the same patients and data set as in their previously mentioned study, applying a new analysis to the images.…”
Section: Muscle Ultrasound In Alsmentioning
confidence: 99%
“…Martínez-Payá et al (2017) also explored muscle textural analysis using the gray-level co-occurrence matrix (GLCM). 32 They used the same patients and data set as in their previously mentioned study, applying a new analysis to the images. GLCM parameters were reduced in patients with ALS, but the authors concluded that combining this measure with echovariance and muscle thickness provided the best discrimination between ALS and control groups.…”
Section: Muscle Ultrasound In Alsmentioning
confidence: 99%
“…Given the recent advent of radiomics that utilizes quantitative imaging features including texture features in oncology and related fields (5,13), there would be little doubt that this methodology of quantitative imaging analysis can be applicable to neuromuscular ultrasound. Indeed, there have been several studies to assess the texture characteristics of skeletal muscles ( 6,12,14,8,(15)(16)(17). Among these, texture analysis of muscle ultrasound was reported to be useful in identifying the underlying etiology (i.e., myogenic vs. neurogenic in nature) (6) and in being potentially utilized as a disease biomarker, such as in amyotrophic lateral sclerosis (17).…”
Section: Clinical Indicationmentioning
confidence: 99%
“…Indeed, there have been several studies to assess the texture characteristics of skeletal muscles ( 6,12,14,8,(15)(16)(17). Among these, texture analysis of muscle ultrasound was reported to be useful in identifying the underlying etiology (i.e., myogenic vs. neurogenic in nature) (6) and in being potentially utilized as a disease biomarker, such as in amyotrophic lateral sclerosis (17). However, before reliably using muscle texture features in any clinical settings, these should be carefully assessed in the confounding factors, such as gender and aging.…”
Section: Clinical Indicationmentioning
confidence: 99%
“…This parameter is highly dependent on the ultrasound device and settings (Pillen and Van Alfen 2015;Zaidman et al 2008). In contrast to mean EI and other first-order descriptors (e.g., standard deviation, skewness, kurtosis and entropy), higher-order texture features (e.g., Haralick features, Galloway features, local binary pattern) have been identified as promising tools for diagnosis, characterization and follow-up of muscle alterations (Konig et al 2015;Martinez-Paya et al 2017;Molinari et al 2015;Sogawa et al 2017;Weng et al 2017). These descriptors may have the advantage of being less affected by variables such as intensity.…”
Section: Introductionmentioning
confidence: 99%